PENGAJARAN SASTRA SEBAGAI UPAYA MEMBENTUK MANUSIA YANG CINTA TANAH AIR: HARAPAN DAN KENYATAAN - Septiningsih, Lustantini (Kajian Linguistik dan Sastra, 2008)
Teaching literature cannot be separated from the existence of literary works. Teaching literature at school can be a tool to improve the lack of studentsâ attitude and morality by introducing and delivering the masterpiece values of Indonesian literary works to the students. By reading the literary works, our nationâs experi- encesâsadness-happiness, bitterness-sweetness, and cleverness-stupidness expe- riencesâwhich occur in the literary works can enrich their religious faiths and make them to be the wise individuals in sharing their own life. This will lead them until they grow up and they will have the fruitful knowledge. One of the main problems occuring in the literature teaching is the mixing of a part of the Indone- sian language teaching materials. The impact influences many things, such the lack of teaching time and students are uninterested in literary works. The literature teaching becomes unpleasant. This paper will oversee the fact that the teaching of literary works in textbooks as samples employed at schools.Â Key words: pengajaran sastra, kurikulum, apresiasi, karya sastra, dan nilai sastra.Â